2002
DOI: 10.1007/3-540-46002-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Black Box Unfolding with Local First Search

Abstract: McMillan's unfolding approach to the reachability problem in 1-safe Petri nets and its later improvements by Esparza-Römer-Vogler have proven in practice as a very effective method to avoid stateexplosion. This method computes a complete finite prefix of the infinite branching process of a net. On the other hand, the Local First Search approach (LFS) was recently introduced as a new partial order reduction technique which characterizes a restricted subset of configurations that need to be explored to check loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Local First Search (LFS) [2,13] is a partial order method to seach for local properties. For a property ϕ, a visible action causes the system to move from a state not satisfying ϕ to a state satisfying it, or vice versa.…”
Section: Extending Trace Systems For Local First Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Local First Search (LFS) [2,13] is a partial order method to seach for local properties. For a property ϕ, a visible action causes the system to move from a state not satisfying ϕ to a state satisfying it, or vice versa.…”
Section: Extending Trace Systems For Local First Searchmentioning
confidence: 99%
“…Given that most of the mentioned specification languages use some kind of interleaving model of automata with shared variables and certain kinds of communication, POEM uses a common data structure as an abstract specification language (it does not have a concrete syntax) that allows comparatively easy translation of specification languages into a unique metalanguage. This paper focuses on the design and the implementation details of traces in POEM, and presents how to extend it to implement Local First Search [2,13]. Moreover, We show the improvement of time consuming of Event Zone approach [11] by combining it with the trace structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, Local First Search (LFS) [11,1] is specialized for the complete search for local properties, i.e. properties that can only be modified by dependent transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], a first method for exploiting this criterion was given, which however did not guarantee that the number of states actually explored would be inferior to the global number of states. In [1] in contrast, the LFS-bound is combined with ideas from McMillan unfoldings [4] to obtain a breadth first search based algorithm that is complete and never explores the same state twice. For a number of benchmarks, it was observed that (asymptotically) LFS with the unfolding approach gives decent reductions where the stubborn set method [17], the ample set [13] and related methods give only very weak reductions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation